Non-surgical cosmetic enhancement: A consumer's legal perspective / Nur Nasrin Adni Salleh … [et al.] - Salleh, Nur Nasrin Adni; Mansor, Alifah Shazwani; Mohamed Noordin, Mohd. Aizuddin; Hamzah, Syahira Rahim (Faculty of Law, 2010)
This research paper outlines the laws and regulations that govern the protection of consumers in non-surgical cosmetic enhancement procedures. It first identifies the issue and the current situation in Malaysia with reference to relevant reported cases. It also includes the identification and analysis of local laws governing the issue, comparison between local laws and international laws as well as problems of enforcement of laws and regulations relating to the issue at the federal and state level. Based on the research done, appropriate recommendations for the protection of consumers in non-surgical cosmetic enhancement procedures apart from the overall conclusion are provided for in Chapter 5 of the paper.